Предмет: Алгебра,
автор: myatamyata
решить уравнение
Ответы
Автор ответа:
0
3x - 6 = x² - 5x + 6
ОДЗ: x² - 5x + 6 ≠ 0, x ≠ 2, x ≠ 3;
x² - 5x + 6 - 3x + 6 = 0
x² - 8x + 12 = 0
x₁ = 2 не удовлетворяет ОДЗ
x₂ = 6
Ответ: х = 6
ОДЗ: x² - 5x + 6 ≠ 0, x ≠ 2, x ≠ 3;
x² - 5x + 6 - 3x + 6 = 0
x² - 8x + 12 = 0
x₁ = 2 не удовлетворяет ОДЗ
x₂ = 6
Ответ: х = 6
Похожие вопросы
Предмет: Українська література,
автор: SoMkaDDR
Предмет: Русский язык,
автор: erikgaripov0
Предмет: Английский язык,
автор: belkatya510400
Предмет: История,
автор: moto55
Предмет: Математика,
автор: анжелика789